Regulatory Cooperation, Aid For Trade And The General Agreement On Trade In Services - Hoekman, Bernard M. 1959- (The World Bank, 2008)
This paper discusses what could be done to expand services trade and investment through a multilateral agreement in the World Trade Organization. A distinction is made between market access liberalization and the regulatory preconditions for benefiting from market opening. The authors argue that prospects for multilateral services liberalization would be enhanced by making national treatment the objective of World Trade Organization services negotiations, thereby clarifying the scope of World Trade Organization commitments for regulators. Moreover, liberalization by smaller and poorer members of the World Trade Organization would be facilitated by complementary actions to strengthen regulatory capacity. If pursued as part of the operationalization of the World Trade Organization's 2006 Aid for Trade taskforce report, the World Trade Organization could become more relevant in promoting not just services liberalization but, more importantly, domestic reforms of services policies